Molecular Dynamics of CH4/N2 Mixtures on a Flexible Graphene Layer: Adsorption and Selectivity Case Study - Vekeman, Jelle; Faginas-Lago, Noelia; Lombardi, Andrea; Sánchez de Merás, Alfredo; García Cuesta, Inmaculada; Rosi, Marzio (Frontiers in Chemistry, 2019)
We theoretically investigate flexible graphene layers, proposing them as membranes of subnanometer size suitable for CH_4/N_2 separation and gas uptake. The potential energy surfaces, representing the intermolecular interactions within the CH_4/N_2 gaseous mixtures and between the graphene layers and the molecules, have been formulated in an internally consistent way. More specifically, by adopting the so-called Improved Lennard-Jones (ILJ) potential, which is far more accurate than the traditional Lennard-Jones potential routinely used to predict static and dynamical properties of matter. Previously derived ILJ force fields are used to perform extensive molecular dynamics simulations on graphene's ability to separate and adsorb the CH_4/N_2 mixture. Furthermore, the intramolecular interactions within graphene were explicitly considered since they are responsible for its flexibility and the consequent out-of-plane movements of the constituting carbon atoms. The influence of introducing flexibility in the graphene sheet on its adsorption ability is assessed via comparison against the adsorption on a rigid graphene sheet. The accuracy of the potentials guarantees a quantitative description of the interactions and realistic results for the dynamics, indicating that the flexible graphene is well capable of separating the CH_4/N_2 mixture. Such properties make these nanostructures versatile materials competitive with other carbon-based adsorbing membranes suitable to cope with CH_4 and N_2 adsorption